2021
DOI: 10.1186/s12985-021-01638-5
|View full text |Cite
|
Sign up to set email alerts
|

Circulating SARS-CoV-2 variants in Italy, October 2020–March 2021

Abstract: A growing number of emerging SARS-CoV-2 variants is being identified worldwide, potentially impacting the effectiveness of current vaccines. We report the data obtained in several Italian regions involved in the SARS-CoV-2 variant monitoring from the beginning of the epidemic and spanning the period from October 2020 to March 2021.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
52
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(56 citation statements)
references
References 12 publications
(8 reference statements)
4
52
0
Order By: Relevance
“…Data obtained in Italy (October 2020 -March 2021) show that the introduction of the UK Alpha variant, corresponded to the second relevant increase of infections registered in Italy during the second epidemic wave [39], when the Military field hospital of Aosta was built [40].…”
Section: Discussionmentioning
confidence: 99%
“…Data obtained in Italy (October 2020 -March 2021) show that the introduction of the UK Alpha variant, corresponded to the second relevant increase of infections registered in Italy during the second epidemic wave [39], when the Military field hospital of Aosta was built [40].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, OSs individuals were likely to be carriers of G clade and its descendents GR and GV, considering their predominance in Italy during the second part of 2020. In particular, since we included samples from November 2020, it is likely that these samples mostly carried the GV clade, which rapidly spread throughout the country and reached a frequency of 96% in December 2020 [ 6 , 8 ]. OSs and αV groups were found to be almost similar in terms of age and gender composition.…”
Section: Discussionmentioning
confidence: 99%
“…To date, several viral strains have been reported. In Italy, the predominant clades from September 2020 to January 2021 were represented by GISAID clade G (lineage B.1, Nextstrain clade 20A) and related clades GR (lineage B.1.1.1, Nextstrain clade 20B and lineage C, Nextstrain clade 20D) and GV (lineage B.1.177, Nextstrain clade 20E, EU1) [ 6 , 7 , 8 ]. Moreover, different Variants Of Concerns (VOCs) occurred, with the alpha variant (αV) (lineage B.1.1.7, GISAID clade GRY, Nextstrain clade 20I/501.Y.V1) and the beta variant (lineage B.1.351, GISAID clade GH, Nextstrain clade 20H/501.Y.V2) being the most relevant for public safety [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we showed that the B.1.1.7 lineage rapidly spread becoming the prevalent lineage from January to March 2021. Indeed, a progressive increase in positive cases of SARS-CoV-2 infections and the concomitant emergence of the Alpha variant were reported in diverse regions of Italy [ 6 , 7 , 15 , 16 ]. Lai and colleagues reported that the B.1.1.7 lineage significantly increased from 3.5% in December 2020 to 86.7% in March 2021, replacing the previously circulating variant B.1.177 [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a progressive increase in positive cases of SARS-CoV-2 infections and the concomitant emergence of the Alpha variant were reported in diverse regions of Italy [ 6 , 7 , 15 , 16 ]. Lai and colleagues reported that the B.1.1.7 lineage significantly increased from 3.5% in December 2020 to 86.7% in March 2021, replacing the previously circulating variant B.1.177 [ 7 ]. Moreover, they assessed that the most important increase in its prevalence was observed from the second week of January to the end of the same month, reaching 73.7% prevalence at the end of February.…”
Section: Discussionmentioning
confidence: 99%